Identification and Analysis of MS5d: A Gene That Affects Double-Strand Break (DSB) Repair during Meiosis I in Brassica napus Microsporocytes - Zeng, Xinhua; Yan, Xiaohong; Yuan, Rong; Li, Keqi; Wu, Yuhua; Liu, Fang; Luo, Junling; Li, Jun; Wu, Gang (Frontiers in Plant Science, 2017)
Here, we report the identification of the Brassica-specific gene MS5d, which is responsible for male sterility in Brassica napus. The MS5d gene is highly expressed in the microsporocyte and encodes a protein that localizes to the nucleus. Light microscopy analyses have demonstrated that the MS5d gene affects microsporocyte meiosis in the thermosensitive genic male sterility line TE5A. Sequence comparisons and genetic complementation revealed a C-to-T transition in MS5d, encoding a Leu-to-Phe (L281F) substitution and causing abnormal male meiosis in TE5A. These findings suggest arrested meiotic chromosome dynamics at pachytene. Furthermore, immunofluorescence analyses showed that double-strand break (DSB) formation and axial elements (AEs) were normal but that DSB repair and spindle behaviour were aberrant in TE5A meiocytes. Collectively, our results indicate that MS5d likely encodes a protein required for chromosomal DSB repair at early stages of meiosis in B. napus.